Letters to a Māori Prophet: Living with Atua in Mid-Nineteenth-Century Taranaki (New Zealand) - Sissons, Jeffrey (Waka Kuaka, 2019)
The focus of this article is a remarkable collection of letters written in the late 1850s to the Māori prophet Tamati Te Ito Ngāmoke of Taranaki (New Zealand). Building on a translation of and introduction to these letters by Penelope Goode, I focus on letters that are concerned with tapu ‘sacredness’ in relation to sorcery and seasonal activities and argue that they provide a unique insight into tapu as an enduring historical condition in relation to which people were required to develop a new mode of collective engagement or correspondence. I conclude with some reflections on the concept of “correspondence” as recently developed by Tim Ingold and consider how, in light of his argument, the Kaingārara letters can be understood as mode of correspondence in a double sense: both as writing and as ontological becoming.